2015
DOI: 10.1177/1090198115599396
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Health by Addressing Basic Needs

Abstract: Members of vulnerable populations have heightened needs for health services. One advantage of integrating health risk assessment and referrals into social service assistance systems such as 2-1-1 is that such systems help callers resolve problems in other areas (e.g. housing). Callers to 2-1-1 in Missouri (N=1090) with at least one behavioral risk factor or cancer screening need were randomly assigned to one of three health referral interventions: verbal referrals only, verbal referrals + a tailored mailed rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…A case management intervention that provided referrals for patient-identified social concerns showed an increased uptake in cancer screening among African American women in Boston; however, no longitudinal patterns were observed (Clark et al, 2009). Thompson, Kreuter, and Boyum (2016) found that individuals who had non–health-related issues resolved through 2-11 social services help line were more likely to follow-up with health referrals (Thompson et al, 2016). Hassan et al (2015) found that a technology-based, patient-centered feedback and referral system for social determinants of health can facilitate screening and connect youth with resources to address health-related social problems.…”
mentioning
confidence: 99%
“…A case management intervention that provided referrals for patient-identified social concerns showed an increased uptake in cancer screening among African American women in Boston; however, no longitudinal patterns were observed (Clark et al, 2009). Thompson, Kreuter, and Boyum (2016) found that individuals who had non–health-related issues resolved through 2-11 social services help line were more likely to follow-up with health referrals (Thompson et al, 2016). Hassan et al (2015) found that a technology-based, patient-centered feedback and referral system for social determinants of health can facilitate screening and connect youth with resources to address health-related social problems.…”
mentioning
confidence: 99%
“…Several recent studies have highlighted the importance of providing additional support to manage the stressors (e.g. lack of food, shelter, safety) that can impede smokers’ ability to engage in programs and make/sustain behavior change [ 31 33 ]. Integrating support for smoking cessation with referrals to community-based resources to address unmet basic needs has shown promise in several studies [ 31 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 These findings are consistent with a growing body of literature showing that programs that coordinate multiple types of social services may reduce health care expenditures or utilization. 11 , 12 , 19 , 32 , 33 Although some programs have targeted specific social determinants of health, such as food insecurity 6 , 9 , 34–36 or housing needs, 7 , 37 , 38 almost half of studies examined in a recent systematic literature review included interventions designed to address multiple unmet social needs. 15 The wide variation of service types represented in Health Connections referral data is consistent with this multi-sector approach.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Similar to 2-1-1 social service information phone lines, the MCO call center representatives refer participants to many different types of social services, including transportation, food programs, financial assistance for utilities, education programs, and housing services. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%